The Effect of Product Quality on Purchase Intention toward Jiniso Products: The Mediating Role of Electronic Word of Mouth (E-WOM) - I Kadek Kian Witko; Ni Ketut Anjani; I Gusti Ngurah Widya Hadi Saputra; I Gst Ayu Wirati Adriati (Economics and Digital Business Review, 2026)
This study aims to analyze the effect of product quality on purchase intention for JINISO products, the effect of product quality on Electronic Word of Mouth (E-WOM), the effect of E-WOM on purchase intention, and the role of E-WOM in mediating the effect of product quality on purchase intention among Generation Z consumers in Denpasar City. Purposive sampling was used in this study's quantitative methodology. Customers between the ages of 17 and 29 who were aware of and have bought JINISO items thru TikTok Shop and followed the TikTok account @Jiniso.id were given questionnaires to complete in order to gather data. With a path coefficient of 0.533, a t-statistic of 6.846, and a p-value < 0.001, the findings demonstrated that product quality had a favorable and substantial impact on purchase intention. With a coefficient of 0.641, a t-statistic of 11.388, and a p-value < 0.001, product quality also significantly and favorably impacted E-WOM. Purchase intention was positively and significantly impacted by E-WOM, with a coefficient of 0.268, a t-statistic of 3.155, and a p-value of 0.002. Furthermore, E-WOM significantly mediated the effect of product quality on purchase intention, with an indirect effect of 0.172. These findings indicate that improving product quality can increase purchase intention both directly and indirectly through E-WOM